A porous organic framework composite embedded with Au nanoparticles: an ultrasensitive electrochemical aptasensor toward detection of oxytetracycline. Issue 40 (30th September 2020) - Han, Zhang-Ye; Zhu, Qian-Qian; Zhang, Han-Wen; Yuan, Rongrong; He, Hongming
Abstract : The fabricated Au@POF-based biosensor has outstanding detectability toward oxytetracycline even in various real samples. Abstract : A porous organic framework (POF) composite embedded with Au nanoparticles (denoted as Au@POF) was fabricated through a toilless impregnation–reduction approach. The as-made Au@POF composite not only has high surface area, excellent physicochemical stability, and favourable electrochemical activity, but also possesses a powerful affinity force toward aptamers to construct an electrochemical aptasensor. As a consequence, a mass of oxytetracycline (OTC) aptamer strands can be loaded onto the surface of the Au@POF-modified electrode to construct a biosensitive platform, which can accurately detect OTC via the unique exclusive interaction between OTC and the aptamer. More importantly, the result indicates that the Au@POF-based aptasensor exhibits supersensitive detectability toward OTC in a certain concentration range from 1.0 × 10 −5 to 1.0 ng mL −1 with a limit of detection of 3.19 fg mL −1 (6.93 fM) as confirmed by electrochemical impedance spectroscopy. By virtue of the merits of high sensitivity, selectivity, stability, repeatability, and straightforward operation, this strategy reveals a potential application in the portable and available detection of OTC even in real samples.